The Effectiveness of Using U-Dictionary Application in Learning English - Cici Yuliyanti; Leroy Holman Siahaan (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
This study uses qualitative research methods to determine the effectiveness of using a u-dictionary application in the learning of English. The data were analyzed using qualitative approaches by the researchers. In this study, questionnaires were employed as research instruments, meetings were held at Google, and interviews were done (open questions). The students of SMK Walisongo Bekasi are the focus of this study. The author takes 20 students using the online dictionary as a sample. The method used by the author is the questionnaire. As a result, it can be concluded that the u-dictionary application can motivate them to learn English because by using this application learning can be easier, faster, and more practical. Meanwhile, students' difficulties in using the u-dictionary application are a bad signal and the lack of funds to fulfill quotas. According to the results of the students' questionnaire, 14 out of 20 students (70%) found the application u-dictionary learning to be highly fascinating. The school should give additional assistance and facilities for instructors and kids to continue using the internet by providing sufficient quota facilities for teachers and other supports, according to policy recommendations. As a result, using the application u-dictionary can help teachers carry out a variety of online teaching and learning activities with their pupils.